Prozesse: Formen, Dynamiken, Erklärungen - Schützeichel, Rainer; Jordan, Stefan (Springer VS, 2015)
Prozessformen -- Prozessdynamiken -- Prozesserklärungen.
Keywords: Aufsatzsammlung; Prozess; Geschichtswissenschaft; Soziologie; Begriff; Sozialer Prozess